Keeping Financial System Clean: Suppressing Terrorist Infiltration of Money or Value Transfer Services in East Africa - NTEGE Edward (Ученые записки Института Африки Российской академии наук)
This article is about understanding the vulnerability of money or value transfer services (MVTS) to terrorist infiltration in East Africa. The author also analyzes the penetration of money transfer services (MVTS) by criminals and their concealment of income as a result of criminal acts. It also examines some of the causal factors of terrorism in the East African region (EA) and describes some effective and comprehensive law enforcement measures aimed at improving the effectiveness and efficiency of the fight against terrorism in the region. The article describes how civil conflicts in the EA region have led to a lack of banking services, which in turn has made EA vulnerable to terrorist financing, further amplified by conflicts in the region that have led to internal and external displacement of migrant communities, societies, and families that rely heavily on transferring funds to dependents. The author examines the consequences of the endless civil war in Somalia by Al-Shabab and how it has led to spread of terrorism and related terrorist financing to neighboring countries. Most of those countries do not have strong anti-money laundering / terrorist financing (AML/CFT) systems. Financial services such as mobile money, Forex bureaus, and other are exposed to high levels of terrorist financing risk in the EA economy. The author goes on to explain how a weak AML / CFT system has led to difficulties or loss of access to International currency markets, and the pressure on relevant banking relationships has in turn undermined and affected the long-term growth prospects and financial accessibility of countries. This led to an increase in the cost of financial services, which negatively affected the banking ratings. Further the author considers the threat to internal and financial stability from criminal activity – in particular, the significant level of tax crimes (value-added fraud and tax evasion) that affect the flow of government revenue, thereby impeding institutional development. This article also highlights how EA member States, through the FATF regional anti-money laundering authority in Eastern and Southern Africa (ESAAMLG), should improve guidelines, strategies and capabilities, such as risk assessment, which is the basis of the MVTS provider’s risk-based approach. They should help money transfer providers understand how and to what extent their services are vulnerable to ML / TF.